Cranio-Caudal Kinematic Turn Signature Assessed with Inertial Systems As a Marker of Mobility Deficits in Parkinson’s Disease - Lebel, Karina; Duval, Christian; Nguyen, Hung Phuc; Plamondon, Réjean; Boissy, Patrick (Frontiers in Neurology, 2018)
Turning is a challenging mobility task requiring proper planning, coordination and postural stability to be executed efficiently. Turn deficits can impair mobility and lead to falls in patients with neurodegenerative disease such as Parkinson’s disease (PD). It was previously shown that the cranio-caudal sequence involved during a turn (i.e. motion is initated by the head, followed by the trunk) exhibits a signature which can be captured using an inertial system and analyzed through the Kinematics Theory. The so-called cranio-caudal kinematic turn signature (CCKS) metrics derived from this approach could therefore be a promising avenue to develop and track markers to measure early mobility deficits. Objective: The current study aims at exploring the discriminative validity and sensitivity of CCKS metrics extracted during turning tasks performed by patients with PD. Methods: Thirty-one participants (16 asymptomatic older adults: mean age = 69.1 ± 7.5 years old; 15 older adults diagnosed with early PD ON and OFF medication, mean age = 65.8 ± 8.4 years old) performed repeated Timed Up and Go tasks while wearing a portable inertial system. CCKS metrics (maximum head to trunk angle reached and commanded amplitudes of the head to trunk neuromuscular system, estimated from a sigma-lognormal model) were extracted from kinematic data recorded during the turn phase of the Timed-Up and Go tasks. For comparison purposes, common metrics used to analyze the quality of a turn using inertial systems were also calculated over the same trials (i.e. the number of steps required to complete the turn and the turn mean and maximum velocities). Results: All CCKS metrics discriminated between older adults and patients (p ≤ 0.041) and were sensitive to change in PD medication state (p ≤ 0.033). Common metrics were also able to discriminate between older adults and patients (p < 0.014), but they were unable to capture the change in medication state this early in the disease (p ≥0.173). Conclusion: The enhanced sensitivity to change of the proposed CCKS metrics suggests a potential use of these metrics for mobility impairments identification and fluctuation assessment, even in the early stages of the disease.